Detection of human papillomavirus type 16 in oropharyngeal squamous cell carcinoma using droplet digital polymerase chain reaction. Issue 10 (17th March 2016) - Biron, Vincent L.; Kostiuk, Morris; Isaac, Andre; Puttagunta, Lakshmi; O'Connell, Daniel A.; Harris, Jeffrey; Côté, David W. J.; Seikaly, Hadi
Abstract : BACKGROUND: The incidence of oropharyngeal squamous cell carcinoma caused by oncogenic HPV (HPV‐OPSCC) is rising worldwide. HPV‐OPSCC is commonly diagnosed by RT‐qPCR of HPV‐16 E6 and E7 oncoproteins or by cyclin‐dependent kinase inhibitor 2A, multiple tumor suppressor 1 (p16) immunohistochemistry (IHC). Droplet digital PCR (ddPCR) has been recently reported as ultra‐sensitive and highly precise method of nucleic acid quantification for biomarker analysis. We aimed to validate this method for the detection of HPV‐16 E6 and E7 in HPV‐OPSCC. METHODS: Participants were recruited from January 2015‐November 2015 at initial presentation to the University of Alberta Head and Neck Oncology Clinic. RNA was extracted, purified and quantified from prospectively collected participant tissues, and ddPCR was performed with fluorescent probes detecting HPV‐16 E6 and E7. Results from ddPCR were compared with p16 IHC performed by clinical pathology as standard of care. RESULTS: Head and neck tissues were prospectively obtained from 68 participants including 29 patients with OPSCC, 29 patients with non‐OPSCC and 10 patients without carcinoma. 79.2% of patients with OPSCC were p16 positive. The sensitivity and specificity of ddPCR HPV E6/E7 compared with p16 IHC in OPSCC was 91.3 and 100%, respectively. The amount of target RNA used was ≤1 ng, 20‐50 times lower than reported by other for RT‐qPCR HPV E6/E7. CONCLUSIONS: The ddPCR of HPV E6/E7 is a novel and highly specific method of detecting HPV‐16 in OPSCC. Cancer 2016;122:1544–51 . © 2016 American Cancer Society . Abstract : The use of recent technology, droplet digital polymerase chain reaction, is described for the enhanced detection of human papillomavirus 16 in oropharyngeal cancer. This method is highly accurate, directly measures oncogenic human papillomavirus, is low cost, and requires smaller patient samples than conventional diagnostics.